Maintenance of Pressing and Touch Cutting Equipment with the Pneumatic System of Subang State Polytechnic - Adhan Efendi; Zainul Ihsan; Yohanes Sinung Nugroho; Annisa Oktaviani (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to make a preventive maintenance plan for tofu presses and cutters with a pneumatic system with the methods carried out namely inspection, small repair, medium repair and overhaul (ISMO). The preventive maintenance time on presses and tofu cutters with this pneumatic system is carried out with this type of maintenance on a monthly and annual basis. The research stages of implementing preventive maintenance on tofu presses and cutters with a pneumatic system includes literature studies, making maintenance schedules and expert validation. Components carried out preventive maintenance on the mechanical system which includes the frame, drive system, compressor and blades. data collection using observation and documentation. data were analyzed descriptively quantitative. The results showed that the preventive maintenance of tofu presses and cutters with a pneumatic system was intended to maintain the condition of the tools as well as to extend their service life and streamline the production process.